Measuring Urban Economic Density - Henderson, J. Vernon; Nigmatulina, Dzhamilya; Kriticos, Sebastian (World Bank, Washington, DC, 2018)
Agglomeration economies are at the heart of urban economics, driving the existence and extent of cities and are central to structural transformation and the urbanization process. This paper evaluates the use of different measures of economic density in assessing urban agglomeration effects, by examining how well they explain household income differences across cities and neighborhoods in six African countries. The paper examines simple scale and density measures and more nuanced ones that capture the extent of clustering within cities. The evidence suggests that more nuanced measures attempting to capture within-city differences in the extent of clustering do no better than a simple density measure in explaining income differences across cities, at least for the current degree of accuracy in measuring clustering. However, simple city scale measures, such as total population, are inferior to density measures and to some degree misleading. The analysis finds large household income premiums from being in bigger and particularly denser cities over rural areas in Africa, indicating that migration pull forces remain very strong in the structural transformation process. Moreover, the marginal effects of increases in urban density on household income are very large, with density elasticities of 0.6. In addition to strong city-level density effects, the analysis finds strong neighborhood effects. For household incomes, overall city density and density of the neighborhood matter.